Religious tolerance among college students: How it's influenced by religious orientation and personality traits? - Abdul Muhid (HUMANITAS: Indonesian Psychological Journal, 2020)
Religious tolerance among college students needs to be maintained to create harmonious conditions and peace among the religious community. This study aimed to explore the influence of religious orientations and personality traits on religious tolerance among college students. This study used a quantitative approach and performed a survey method that utilized three measurement tools of psychological scales: the Religious Orientation Scale-Revised, the Personality Scale of Big Five Personality and the Scale of Religious Tolerance. The subjects of this study were 280 students from six universities in Surabaya. The results of the study show that, generally, there is a significant influence of religious orientation and personality traits on religious tolerance among college students. Partially, intrinsic religious orientation has a positive influence on religious tolerance, and on the contrary, the extrinsic religious orientation has a negative influence on religious tolerance. Of the personality traits (Big Five Personality), agreeableness and openness have a positive influence on religious tolerance. Meanwhile, extroversion, conscientiousness, and neuroticism do not have a significant influence on religious tolerance. Therefore intrinsic religious orientation and two personality traits - agreeableness and openness - are important to develop religious tolerance among college students. While college student who have extrinsic religious orientation tend to have low religious tolerance.